O MÉTODO FILOSÓFICO DE MARX: Uma proposta de sequência didática para o ensino médio. - ANDRÉ LEONARDO PEREIRA DA SILVA (2025)
The main objective of this dissertation is to contribute to the education of students and education professionals through the study of the dialectical exposition of Karl Marx's Capital. It also seeks to reproduce concepts found in the book, together with the analysis of other writers and researchers who detail some of the main concepts present in chapter 1 of Capital, serving as examples the concepts of concrete labor, abstract labor, commodity and value, in addition to commodity fetishism. The objective is to produce a didactic sequence to encourage reflection on the economic way of life in capitalism and to observe the contradictions that exist in everyday life, issues that can contribute significantly to awakening the critical sense in the learning of philosophy. The intention is, therefore, to explain the exposition and the dialectical method used by Marx, present in chapter 1 of his magnum opus, Capital, seeking a simple and accessible language for high school students, unlike overly theoretical materials. The elaboration of this didactic sequence is expected to show the importance of Marx for philosophy and how he shaped human history and interfered in thousands of minds. The aim is to draw an analogy with current situations, as well as to pay attention to the current mode of consumption. The aim is, then, with this objective discussion and the deepening of the concepts idealized by Marx, to extract the multiplicity of thoughts that can contribute to observations and questions, thus bringing a great reflective and philosophical contribution.